One-stage fluoroscopic-guided laparoscopic transcystic papillary balloon dilation and laparoscopic cholecystectomy for the treatment of choledocholithiasis after Roux-en-Y reconstruction - Kamada, Teppei (BMJ Case Rep, 2020)
Patients with a history of gastrectomy have a higher incidence of cholecystocholedocholithiasis and morbidities. In particular, the management of choledocholithiasis with endoscopic retrograde cholangiopancreatography (ERCP) has been challenging in patients after Roux-en-Y or Billroth II reconstruction due to the altered gastrointestinal anatomy. A 92-year-old man presented with high fever. He had undergone laparoscopic distal gastrectomy with Roux-en-Y reconstruction 9 years earlier for gastric cancer. Choledocholithiasis was diagnosed and ERCP was attempted, but cannulation of the papilla of Vater failed. An elective one-stage operation was planned. One-stage fluoroscopic-guided laparoscopic transcystic papillary balloon dilation (LTPBD) and laparoscopic cholecystectomy (LC) were performed. The operation time was 130 min with 3 mL of intraoperative bleeding. The patient was discharged on postoperative day 3 with no complications. We report this case in which one-stage LTPBD and LC was successfully performed for a super-elderly patient with choledocholithiasis after Roux-en-Y reconstruction.